Signal Processing Techniques for Through-Wall Object Imaging Using UWB Antipodal Vivaldi Antenna - Sajjad Ahmed; Arslan Ahmed Sohoo; Fawad Salam Khan; Imran Khan Keerio; Sarfraz Ahmed (JISR on Computing, 2024)
Through-wall imaging (TWI) is a critical application in various domains, including security, surveillance, search and rescue, and structural assessment. This paper investigates signal processing techniques to achieve object imaging through walls using an Ultra-Wideband (UWB) Antipodal Vivaldi antenna (AVA). The design and simulation of the UWB AVA antenna optimized for TWI are presented. The antenna exhibits wide bandwidth, low sidelobes, and directional radiation patterns, making them suitable for capturing weak signals reflected from hidden objects. Signal processing plays a crucial role in extracting valuable information from TWI. In this investigation, the focus lies on analyzing time domain signals for TWI, studying the factors influencing the process, and successfully retrieving two-dimensional details of the scanned scene. The proposed approach leverages the unique characteristics of UWB signals, such as their ability to penetrate obstacles and provide fine spatial resolution.